2009
DOI: 10.1107/s0021889809013430
|View full text |Cite
|
Sign up to set email alerts
|

The pseudo-single-crystal method: a third approach to crystal structure determination

Abstract: A novel method that enables single-crystal diffraction data to be obtained from a powder sample is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 7 publications
(7 reference statements)
0
49
0
Order By: Relevance
“…The MOMA method is applicable to the biaxial crystal systems including the triclinic, monoclinic, and orthorhombic systems. We have reported the X-ray measurements of MOMAs fabricated from L-alanine [15], LiCoPO 4 [16], sucrose [17], and lysozyme [19] microcrystalline powders, which gave rise to diffraction patterns similar to those of the corresponding single crystals. The crystal structures determined from the MOMAs were in good agreement with those reported for the corresponding single crystals in the literature.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The MOMA method is applicable to the biaxial crystal systems including the triclinic, monoclinic, and orthorhombic systems. We have reported the X-ray measurements of MOMAs fabricated from L-alanine [15], LiCoPO 4 [16], sucrose [17], and lysozyme [19] microcrystalline powders, which gave rise to diffraction patterns similar to those of the corresponding single crystals. The crystal structures determined from the MOMAs were in good agreement with those reported for the corresponding single crystals in the literature.…”
Section: Introductionmentioning
confidence: 90%
“…A MOMA is a composite in which microcrystals are aligned three-dimensionally [14][15][16][17][18][19]. The concept of the three-dimensional crystal alignment was reported in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that magnetic field effect (MFE) on α-γ transformation and the microstructure of steel [2,3], melting behavior of diamagnetic materials under the magnetic levitation [4], the three-dimensional crystal orientation of proteins [5], the crystallization of the amorphous [6], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to discover and develop new materials, the magnetic-field effect (MFE) on, for example, diffusion coefficients [2,3], crystal orientations [4,5], microstructures [6,7], and phase equilibria [8][9][10], have been studied worldwide using high-field magnets. However, to observe these phenomena at high temperatures and 1-T magnetic fields is very difficult using conventional equipment.…”
Section: Introductionmentioning
confidence: 99%